INFORMATION-MEASURING TEST SYSTEM OF DIESEL LOCOMOTIVE HYDRAULIC TRANSMISSIONS - Zhukovytskyy, I. V.; Kliushnyk, I. A.; Ochkasov, O. B.; Korenyuk, R. O. (Science and Transport Progress, 2015)
Purpose. The article describes the process of developing the information-measuring test system of diesel locomotives hydraulic transmission, which gives the possibility to obtain baseline data to conduct further studies for the determination of the technical condition of diesel locomotives hydraulic transmission. The improvement of factory technology of post-repair tests of hydraulic transmissions by automating the existing hydraulic transmission test stands according to the specifications of the diesel locomotive repair enterprises was analyzed. It is achieved based on a detailed review of existing foreign information-measuring test systems for hydraulic transmission of diesel locomotives, BelAZ earthmover, aircraft tug, slag car, truck, BelAZ wheel dozer, some brands of tractors, etc. The problem for creation the information-measuring test systems for diesel locomotive hydraulic transmission is being solved, starting in the first place from the possibility of automation of the existing test stand of diesel locomotives hydraulic transmission at Dnipropetrovsk Diesel Locomotive Repair Plant "Promteplovoz". Methodology. In the work the researchers proposed the method to create a microprocessor automated system of diesel locomotives hydraulic transmission stand testing in the locomotive plant conditions. It acts by justifying the selection of the necessary sensors, as well as the application of the necessary hardware and software for information-measuring systems. Findings. Based on the conducted analysis there was grounded the necessity of improvement the plant hydraulic transmission stand testing by creating a microprocessor testing system, supported by the experience of developing such systems abroad. Further research should be aimed to improve the accuracy and frequency of data collection by adopting the more modern and reliable sensors in tandem with the use of filtering software for electromagnetic and other interference. Originality. The authors developed the information-measuring system that improves the hydraulic transmission test process by automating and increasing the accuracy of measurements of control parameters. The measurement results are initial data for carrying out further studies to determine the technical condition of the hydraulic transmission UGP750-1200 during the plant post-repair tests. Practical value. The paper proposed the alternate design of microprocessor hydraulic transmission test system for diesel locomotives, which has no analogues in Ukraine. Automated data collection during the tests will allow capturing the fast processes to determine the technical condition of hydraulic transmission.